Impact of synthetic surfactants and oil dispersants on the gills of juvenile gilthead (Sparus aurata L.) - Maria Angela Masini; Paola Prato; Elisabetta Giacco; Gian Luigi Mariottini; Luigi Pane (Journal of Biological Research, 2014)
Histological, scanning electron microscopic and immunohistochemical studies were performed on the gills of juvenile gilthead (Sparus aurata L.) exposed to various concentrations of three anionic detergents: sodium dodecyl sulphate (SDS), safety sea cleaner 2 (SSC2), and FINASOL OSR2, in short term (96 h) and chronic (28 days) experiments. The mortality rate, median lethal concentration (LC50) and the no observed effect concentration (NOEC), were calculated. At concentrations above 10 mg/L, mortality was from 50 to 100% after exposure to SDS and SSC2, both in short term and chronic experiments. Gills were spongiotic and there were many lamellar fusions, membrane disruptions, hydropic degenerations and exfoliations of lamellar and interlamellar epithelium after 96 h of treatment and more markedly after chronic experiment. Microridges of the cell surface were less evident or absent. The enzymes of ion transport were down regulated. Exposure to FINASOL OSR2 (100 mg/L) showed no evident branchial alteration.